The Effect of Phosphodiesterase 5 Inhibitor on Biochemical Recurrence Following Radical Prostatectomy in Patients with Prostate Cancer - Chung, Jae-Wook; Kim, Jin Woo; Ha, Yun-Sok; Choi, Seock Hwan; Lee, Jun Nyung; Kim, Bum Soo; Kim, Hyun Tae; Yoo, Eun Sang; Kwon, Tae Gyun; Kim, Tae-Hwan (Urology Journal, 2019)
Purpose: Recently, controversy exists regarding the oncologic outcomes associated with the use of phosphodiesterase 5 inhibitor (PDE5i). Therefore, we attempted to verify the effect of PDE5i on biochemical recurrence (BCR) following radical prostatectomy (RP) in patients with prostate cancer (PCa). Materials and Methods: From January 2011 to May 2016, 351 patients who had undergone bilateral neurovascular bundle saving and who were confirmed as having pT2N0M0 disease were included in the present study. We divided these patients into three groups: no PDE5i use, PDE5i use on demand , and PDE5i use for rehabilitation. We retrospectively analyzed the effect of PDE5i on BCR of PCa. Mean follow-up period was 34.4 months and mesurement of outcome was whether the patients developed BCR during regular follow-up. Results: 25 (7.1%) patients showed BCR and univariate analysis found no significant differences in BCR between the three groups (5 (6.9%) in no PDE5i use, 8 (9.5%) in PDE5i use on demand, 12 (6.2%) in PDE5i use for rehabilitation). Multivariable analyses showed that treatment type was not a significant factor for BCR between the groups with no PDE5i use and PDE5i use (HR = 1.34 [0.49–3.70]; P = .573) and between the groups with on demand and rehabilitation use (HR = 1.37 [0.35–5.37]; P = .646). Kaplan-Meier survival curves show that there were no significant differences in PSA recurrence-free survival in three groups (P > .05). Conclusion: Use of PDE5is was not associated with any adverse effects on BCR after RP in patients with PCa.